High amplitude and low frequency cyclic mechanical strain promotes degeneration of human nucleus pulposus cells via the NF‐κB p65 pathway. Issue 9 (25th March 2018) - Wang, Shengjie; Li, Jie; Tian, Jiwei; Yu, Zhenghong; Gao, Kun; Shao, Jia; Li, Ang; Xing, Shuai; Dong, Yonghui; Li, Zhiyong; Gao, Yanzheng; Wang, Liping; et al.
Abstract : Disc degeneration alters the structure and function of intervertebral discs and is the basis of spinal degenerative diseases. To establish the molecular mechanism of intervertebral disc degeneration caused by mechanical strain, this study examined the effects of different amplitude (3%, 9%, 19%) cyclic mechanical strain (CMS) at a low frequency (0.01 Hz) on the secretion of cartilage extracellular matrix, expression of inflammatory cytokines and catabolic proteases, and activation of NF‐κB signaling pathway in human nucleus pulposus cells. We also investigated effects of low frequency and high amplitude (19%) CMS on degeneration of human nucleus pulposus cells in the presence or absence of p65 inhibitor, p65 silencing shRNA, or p65 overexpression. While 3% CMS did not significantly decrease aggrecan or type II collagen expression, or increase TNF‐α, IL‐1β, IL‐6 expression, 9% and 19% CMS showed the significant effects. Low frequency and high amplitude (19%) CMS was found to promote p65 activation in human nucleus pulposus cells, and IL‐1β was found to promote p65 nuclear translocation though IκB kinase phosphorylation. Furthermore, degeneration process of nucleus pulposus cells was found attenuated in the presence of p65 inhibitor or p65 silencing shRNA, but promoted with p65 overexpression. These data suggest that high amplitude and low frequency CMS could promote degeneration of human nucleus pulposus cells significantly via the NF‐κB p65 pathway. Our findings have uncovered the effect of CMS on human nucleus pulposus cell degeneration and have identified a previously unknown intrinsic underlying mechanism. Abstract : Low frequency and high amplitude (19%) CMS was found to promote p65 activation in human nucleus pulposus cells, and IL‐1β was found to promote p65 nuclear translocation though IκB kinase phosphorylation. Furthermore, degeneration process of nucleus pulposus cells was found attenuated in the presence of p65 inhibitor or p65 silencing shRNA, but promoted with p65 overexpression. These data suggest that high amplitude and low frequency CMS could promote degeneration of human nucleus pulposus cells significantly via the NF‐κB p65 pathway. Our findings have uncovered the effect of CMS on human nucleus pulposus cell degeneration and have identified a previously unknown intrinsic underlying mechanism.